Seasonality of Response to Millennial‐Scale Climate Events of the Last Glacial: Evidence From Loess Records Over Mid‐Latitude Asia. (21st October 2021) - Fan, Yijiao; Jia, Jia; Xia, Dunsheng; Meadows, Michael; Wang, Zhiyuan
Abstract: Although difficult to resolve, seasonality is an important element in considering paleoenvironmental records and simulated results, and it is therefore critical to address this shortcoming in order to develop more accurate reconstructions of past climate. In this study, climatic proxies with seasonal implications (magnetic susceptibility and mean grain size) are analyzed for several high‐resolution loess sections from mid‐latitude Asia using the Ensemble Empirical Mode Decomposition (EEMD) to detect their response to millennial‐scale oscillations during the last glaciation. In so doing, we are capable to estimate the amplitude and relative contribution of the reconstructed climate components. Combined with an analysis of modern processes, magnetic susceptibility ( χ ) can be interpreted as representing summer and spring precipitation, while mean grain size (Mz) can be interpreted as representing spring and summer dust activity in the Chinese Loess Plateau (CLP) and southern central Asia (SCA), respectively. Our results show that the spring and summer signals are clearly correlated with Heinrich events, but that the spring signal is more prominent than the summer signal during Dansgaard‐Oeschger (D‐O) oscillations of the last glacial. These results are consistent with modeled simulations. It is proposed that weakening or complete shutdown of AMOC influences the response of seasonal signals to abrupt climate events. The study highlights the need for further high‐resolution climate proxies with robust seasonality indicators in order to develop a deeper understanding of the response of mid‐latitude Asia to rapid climate events. Key Points: The climate over mid‐latitude Asia presented seasonal response to abrupt climate events during the last glacial Spring climate is more sensitive to millennial‐scale abrupt events than summer The weakening and closing of the Atlantic meridional overturning circulation influence the seasonal response